Evidence of persistent Mullerian duct syndrome in a Yorkshire terrier - Silva, Priscila; Uscategui, Ricardo A. R.; Gatto, Igor R. H.; De Brito, Marina B. S.; Simões, Ana Paula R.; Almeida, Vivian T.; Feliciano, Marcus A. R.; Vicente, Wilter R. R. (Revista Colombiana de Ciencias Pecuarias, 2018)
Anamnesis: A one-year-old female Yorkshire terrier, weighing 2.2 kg, was referred for evaluation of an abnormal structure in the inguinal region. Clinical and laboratory findings: Upon examination, the structure -similar to a penis- was found protruding from the preputial orifice. Physical, laboratory, ultrasound, and radiographic examinations were performed. The initial suspicion was a case of sexual development disorder, so the dog was referred for exploratory laparotomy and karyotyping. Treatment approach: During the surgical procedure, two macroscopically similar structures were found at the caudal pole of the left and right kidneys. These tissues were attached to two structures similar to the uterine horns, caudally fused to a body in the pelvic cavity. All the tissue was removed and submitted for histopathological examination, revealing the presence of typical seminiferous tubules (testis) and proliferative endometrial glands (uterine tubes). Subsequently, a surgical correction procedure was performed to cover the penile tissue and avoid damage by exposure and contact. Conclusion: This case reports unique information on diagnosis and therapeutic approach in a Yorkshire terrier with persistent Müllerian duct syndrome (PMDS). Because they are unusual, sexual development disorders are challenging in terms of diagnostic and therapy, making this report a valuable tool for veterinarians.